Experiment design for environmental engineering : methods and examples - Hopcroft, Francis J.; Charest, Abigail (BOCA RATON: CRC, 2022)
"This book provides a wide range of practical environmental engineering laboratory experiments for implementation by students in a university laboratory or by practicing professionals in the field, along with an extensive discussion on how to design an experiment that will provide meaningful and useful data, how to interpret the data generated from an experiment, and how to present those data to an audience of other students or professionals. The example experiments provide a way to evaluate a new design against an existing experiment to determine what information is most appropriate in each section and how to format the data for the most effective outcome"--
Includes bibliographical references and index.
Keywords: Environmental sciences; Environmental engineering; Pollution; Experimental design